Design and fabrication of fiber-based surface plasmon resonance sensors - Al-Qazwini, Yusser A. Taqi (2016)
Surface plasmon resonance (SPR) sensors based on optical fibers, with their high level of miniaturization, high sensitivity to variations in the refractive index (RI) of the surrounding medium, and sensing capability in hazardous areas, have attracted a great attention for the past two decades as one of the most advanced real-time and label-free detection technology. The performance of these devices in terms of their sensitivity and detection accuracy is of great importance and it is strongly influenced by the design parameters such as fiber material and geometry, and the properties of the metal layer and sensing medium. This thesis presents numerical simulations to understand the impact of these parameters on the performance of a basic fiber-based SPR sensor implementing a simple waveguide layered structure. The thesis also reports the fabrication of two cost-effective fiber-based SPR sensors. The developed sensors are tested for RI sensing of aqueous media.A simple planar layered structure is numerically simulated to provide design specifications for fiber-based SPR sensors. The numerical simulations help understand the influence of the properties of the involved layers like metal layer and residual cladding thickness, sensing length, and RI of the sensing medium on the response of SPR sensors. An SPR sensor based on a tapered multimode fiber is fabricated and experimentally characterized for its performance. The sensor is made by tapering a standard multimode fiber using an automated tapering machine followed by coating the entire taper with gold without masking. The impact of waist-diameter, waist and transition lengths on the performance of the sensor is investigated. A simple, high-performance, yet robust sensor with a spectral width of 140-220 nm and a sensitivity of ~1600-2000 nm/RIU is realized when the waist diameter is set to 25-45 μm with a total taper length of 3-5 mm and 55-nm gold thickness.A second configuration based on plastic optical fiber is fabricated and analyzed. This fiber brings additional advantages to SPR sensors because of its large numerical aperture, excellent flexibility, and easy manipulation. The implemented chemical etching process with concentrated Acetone preserves the fiber’s circular geometry which simplifies the fabrication process and reduces the associated costs compared to side-polished ones. Same setup and sensing solutions are used while the influence of the gold thickness, fiber residual thickness, and sensing length is investigated. A low-cost, sensitive, and robust SPR sensor with an average sensitivity of 1600 nm/RIU and spectral width of 154 nm is realized when a plastic optical fiber is etched from the middle up to 964-μm with 10-mm sensing length and 55-nm gold thickness.